Experimental evaluation of the heat flux induced by tunnel fires. (November 2016) - Shaw, Timothy; Gibson, Timothy; Karlovšek, Jurij; Emberley, Richard; Torero, José L.
Abstract: Traffic tunnel closures are highly undesirable and some of the lengthiest are attributed to structural failures. Historical data shows that these failures are closely linked to fire. Furthermore, the parameters necessary for proper thermo-mechanical analysis of structural members are poorly defined or absent from literature. The energy transferred to the structure (i.e. heat flux) is the fundamental parameter for determining structural performance in fire. However, current research focuses on identifying heat release rates and temperature histories which are difficult to use for structural analyses. In this study, full-scale experiments were undertaken on passenger vehicles resulting in heat fluxes between 20 and 70 kW/m 2 . The analyses show fire duration is linked to a vehicle's mass and small vehicle fires can be scaled as a function of the ratio between the tunnel diameter and the characteristic height of the desired vehicle. Appropriate design values are outlined for engineers to undertake informed thermo-mechanical analyses to minimise the risk of structural tunnel failure in fires.